Understanding customer brand engagement in brand communities: an application of psychological ownership theory and congruity theory. (23rd January 2021) - Kumar, Jitender
Abstract : Purpose: The purpose of this study is the exploration of customer engagement with the brand and brand community (dual foci) inside online brand communities and to assess the simultaneous impact of dual foci of engagement in creating equity for the brand. The role of sense of community is explored as a moderator in influencing customer engagement. Design/methodology/approach: The sample is composed of the members of Facebook-based brand communities. An internet survey of 833 subjects provides data to test the theoretical model with the help of structural equation modelling using AMOS 21. Findings: The empirical investigation supports the proposed theory except for a few counterintuitive findings. Psychological ownership with the brand and the brand community has a direct effect on customer engagement with the brand and the brand community, respectively. A brand-based value-congruity has a direct effect on brand engagement; however, community-based value-congruity has an indirect effect on brand community engagement through brand community psychological ownership. The moderating effect of sense of community on engagement is also observed. Engagement with dual foci explained a substantial proportion of the variance in brand equity. Research limitations/implications: A student sample, cross-sectional research design and a limited number of constructs in the nomological network to explore engagement in an online brand community constitute few limitations of this study. Customer engagement with dual foci has major implications for both the researchers and practitioners dealing with online brand communities. Practical implications: To engage customers in online brand communities, dual foci should be the objective of management. A sense of ownership towards the brand and value-congruity with the brand should be aimed to engage customers with the brands; brand community psychological ownership and value-congruity with the community should be embraced by the firms to achieve brand community engagement. A high sense of community also needs to be promoted for strengthening dual foci engagement that further generates brand equity. Originality/value: Customer brand engagement and brand community engagement had been studied separately in literature ignoring the fact that brand is the raison d'etre of the community. Taking a dual object engagement perspective, this study has charted out different routes of how to generate brand equity using online brand communities.